Cemaran Mikrobiologis Pada Beberapa Loloh Bali Di Kota Denpasar - Sandhi Wipradnyadewi, Putu Ari; Ari Yusasrini, Ni Luh (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 4 No 1 (2017), 2017)
The purpose of this study was to determine the amount of microbial contamination and bacterial pathogens as well as the level of safety on some of loloh Bali in Denpasar. The study consisted of two phases i.e. first: an inventory of some loloh Bali in Denpasar, among others, loloh don base, loloh don sirsak, loloh don jarak, loloh samiloto, loloh don tempuyak, loloh kunyit, loloh temulawak and loloh don piduh. The second stage: the analysis of microbial contamination and bacterial pathogens of loloh Bali In the first stage concluded that there were loloh don base, loloh don sirsak, loloh don jarak, loloh samiloto, loloh don tempuyak, loloh kunyit, loloh don piduh and loloh temulawak in Denpasar. The second phase resulted that 100% of the samples loloh don base, don piduh, don sirsak, don jarak, and don tempuyak compliant with the value of total microbes, 16.7% of the samples loloh samiloto, 75% loloh kunyit and 50% loloh temulawak meet the requirements of total microbes. 100% of loloh don piduh, 16.7% loloh don base, 0% loloh samiloto, 0% loloh don sirsak, 0% loloh don jarak, 0% loloh don tempuyak, 75% loloh kunyit and 50% loloh temulawak meet the requirementsof total coliform and 100% of the samples have been analyzed showed did not contain E.coli. Loloh don base 4, loloh kunyit 2, loloh kunyit 4, loloh don piduh meet all the requirements of total microbes, coliform and E. Coli.